OLIY TA’LIM MUASSASALARIDA ARALASH TA’LIM METODIKASIDAN FOYDALANISH - Aytimbetova, U. (SCIENCE and SOCIETY, 2023)
The article examines the concept of blended learning, its purpose, and current importance. The development of mixed education methodology and the use of mixed education models to increase students’ interest in learning and achieve effective results in teaching, as well as its advantages and disadvantages are presented.